HHSRP: a cluster based hybrid hierarchical secure routing protocol for wireless sensor networks - Deepa, C.; Latha, B. (Cluster computing, 2019)
Wireless sensor networks happen to be fundamentally networks with energy restrictions. This is limited over longer period of time proves to be the challenge in clustering algorithms. We suggested a new method related to co-ordinator head (CNH) selection by using a mixed hierarchical cluster based algorithm that includes selecting the CNH happens to be the greatest value of the co-ordinator node (CN) and fitness value. This analysis put forward two different algorithms; mixed hierarchical cluster oriented routing program and hybrid hierarchical secure algorithm. A mixed hierarchal cluster based algorithm has been suggested for generating CNH and CN, for identifying the harmful node and packet is securely delivered. The source node transmits details about packet to the CN and then it chooses the pathway which is the shortest, depending upon the trust value among intermediate node and sensor node. The behavior activities of all the nodes are analyzed by the CNH, if anyone of the node’s behavior found to be incorrect, the organizer who finds the harmful node and CNH will drop those particular node behaviors. The CNH then changes to other path way immediately and transmits the delivery packet securely to the target destination under short time.